Analisa Pendekatan Integratif Menggunakan Metode Six Sigma dan RCA pada Kualitas Kemasan Pupuk Granule - Dimas Dwi Saputra; Atikha Sidhi Cahyana (Indonesian Journal Publisher, 2024)
This research was conducted at a company engaged in product packaging. Companies face one challenge, namely the increasing percentage of defects in fertilizer packaging by 0.5% to 1.7%. This research aims to identify the types of defects in granule fertilizer packaging, find out the causes of defects, and find out the root of the problem of defects and provide recommendations for improvement. The six sigma method is used with integrated root cause analysis (RCA). Six sigma is used to determine the sigma value. RCA to find out the cause and root of the problem. The results of this research show that the company's average sigma value is 3.52. With DMAIC and RCA approaches, it can be seen that the causes and root causes of product defects are caused by 4 factors, namely machines, materials, people and methods, so it is necessary to maintain machines, monitor raw materials and train employees